2018
DOI: 10.1002/jcc.25595
|View full text |Cite
|
Sign up to set email alerts
|

A computational foray into the mechanism and catalysis of the adduct formation reaction of guanine with crotonaldehyde

Abstract: Crotonaldehyde, a common environmental pollutant and product of endogenous lipid peroxidation, reacts with guanine to form DNA adducts with pronounced genotoxicity and mutagenicity. Here, we explore the molecular mechanism of this adduct formation using double‐hybrid density functional theory methods. The reaction can be envisaged to occur in a two‐step fashion via an aza‐Michael addition leading to an intermediate ring‐open adduct followed by a cyclization reaction giving the mutagenic ring‐closed adduct. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…A further mechanism for keto‐enol tautomerizations is available, involving concerted movement of two protons between the substrate and an acid catalyst molecule, such as formic acid. Further studies have shown that acid catalyzed double hydrogen atom transfer reactions occur in a wide variety of situations, including other tautomerizations, decomposition and bimolecular reactions, and in keto‐enol tautomerizations of dimer complexes . Furthermore, this mechanism may also play a role in the isomerization of free radicals, in the hydration of SO 3 , and in the hydrolysis of carbonyl compounds in the atmosphere, as well as in the unimolecular rearrangement of oxygenated volatile organic compounds …”
Section: Introductionmentioning
confidence: 99%
“…A further mechanism for keto‐enol tautomerizations is available, involving concerted movement of two protons between the substrate and an acid catalyst molecule, such as formic acid. Further studies have shown that acid catalyzed double hydrogen atom transfer reactions occur in a wide variety of situations, including other tautomerizations, decomposition and bimolecular reactions, and in keto‐enol tautomerizations of dimer complexes . Furthermore, this mechanism may also play a role in the isomerization of free radicals, in the hydration of SO 3 , and in the hydrolysis of carbonyl compounds in the atmosphere, as well as in the unimolecular rearrangement of oxygenated volatile organic compounds …”
Section: Introductionmentioning
confidence: 99%